1997
DOI: 10.1002/(sici)1097-4660(199705)69:1<35::aid-jctb685>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Rates for the Partial Dehydration of Glucose to Organic Acids in Solid-Acid, Molecular-Sieving Catalyst Powders

Abstract: Molecular‐sieving catalysts have the potential to promote the production of oxygenated hydrocarbons from glucose. A kinetic model for the partial dehydration of glucose to organic acids by micro‐ and mesoporous aluminosilicate catalysts was developed. Kinetic parameters were estimated from glucose conversion and product yield versus time data at 150°C for HY‐zeolite, aluminum‐pillared montmorillonite, MCM‐20 and MCM‐41 catalyst powders of 0·5 mmol H+ g−1 solid‐acid activity. Rate constants for the partial dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 0 publications
6
45
0
Order By: Relevance
“…It can serve in the dehydration of glucose [7][8][9]. Moreover, to promote the conversion of glucose, several solid acids including ion-exchange resins [10], solid phosphates [11][12][13], metal oxides [14,15], and zeolites [16][17][18][19][20][21] From current studies, zeolites show a potential use in glucose dehydration and it is found that the pore structure has a significant influence on the reaction [16][17][18][19][20]22]. Thus, in this work, we employed a novel MFI-type zeolite, denoted as ZRP, in the glucose dehydration reaction.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…It can serve in the dehydration of glucose [7][8][9]. Moreover, to promote the conversion of glucose, several solid acids including ion-exchange resins [10], solid phosphates [11][12][13], metal oxides [14,15], and zeolites [16][17][18][19][20][21] From current studies, zeolites show a potential use in glucose dehydration and it is found that the pore structure has a significant influence on the reaction [16][17][18][19][20]22]. Thus, in this work, we employed a novel MFI-type zeolite, denoted as ZRP, in the glucose dehydration reaction.…”
Section: Introductionmentioning
confidence: 65%
“…However, the highest yield of LA is obtained on ZRP-30, not on ZRP-25. The highest yield of LA is 35.8%, which is higher than the value obtained on other zeolites [16][17][18][19]. Formic acid, which is formed coupling with LA from HMF, has a Dehydration of glucose to levulinic acid 379 higher yield than that of LA.…”
Section: Resultsmentioning
confidence: 99%
“…These thermally stable oxygenates are intermediates in the production of aromatics. The furan compounds are formed from acid catalyzed dehydration of carbohydrates [24]. The acid catalyst can be both the heterogeneous solid acid and the homogenous organic acid products.…”
Section: Catalyst-to-feed Ratiomentioning
confidence: 99%
“…It is well possible that the salt promotes the isomerisation of D-glucose to D-mannose and D-fructose. This isomerisation reaction is well known to be catalysed by solids (cation ion exchange resins, hydrotalcites and metal oxides such as ZrO 2 and TiO 2 ) and involves an 1,2-enediol as the intermediate [10,[22][23][24]. The D-fructose and D-mannose formed in the isomerisation reaction are not inert and also known to react to, among others, HMF and levulinic acid [1].…”
Section: Development Of a Reaction Networkmentioning
confidence: 99%
“…A wide variety of Bronsted acid catalysts have been tested for these conversions. Examples are homogeneous catalysts like sulfuric acid, hydrochloric acid, phosphoric acid, trifluoroacetic acid [3,8,9] and solid acid catalysts like acidic ion exchange resins, zeolites and montmorillonites [10].…”
Section: Introductionmentioning
confidence: 99%